Liberalization, Hindu nationalism, and the state a biography of Gujarat - Sud, Nikita, 1978- (New Delhi ; Oxford : Oxford University Press, 2012)
This is a comprehensive account of the post-independence history and politics of Gujarat, using a macro, long-term perspective. It examines the co-existence of economic liberalism and political illiberalism in the state and analyses its relevance to India's growth story.
Description based on online resource; title from PDF title page (viewed on Aug. 13, 2012).
Includes bibliographical references and index.
Keywords: Gujarat (India) -- History -- 20th century; Gujarat (India) -- History -- 21st century; Gujarat (India) -- Politics and government -- 20th century; Gujarat (India) -- Politics and government -- 21st century; Hindutva -- India -- Gujarat